Efektivitas Terapi Audio Murottal Al-Qur’an Surah Ar-Rahman terhadap Halusinasi Pendengaran pada Pasien Skizofrenia di Panti Gramesia Cirebonnti Gramesia Cirebon - Putri Nurfitriani; Reni Purwo Aniarti; Mawar Amanda (PPNI UNIMMAN, 2025)
Auditory hallucinations are one of the main symptoms experienced by patients with schizophrenia. Non-pharmacological interventions, such as spiritual therapy, serve as important alternatives to support treatment. One increasingly used method is the recitation of Qur’anic verses (murottal therapy), which provides psychological and spiritual calming effects. To determine the impact of murottal audio therapy of Surah Ar-Rahman on the intensity of auditory hallucinations in patients with schizophrenia at Gramesia Nursing Home, Cirebon. This scientific paper is presented in the form of a nursing care report focusing on the application of murottal audio therapy using Surah Ar-Rahman as an intervention. Before the therapy, the patient experienced moderate auditory hallucinations, accompanied by intense emotional reactions and difficulty controlling behavior. After undergoing murottal audio therapy, there was a decrease in hallucination intensity and improvement in the patient’s emotional condition. Murottal audio therapy of Surah Ar-Rahman is effective as a non-pharmacological approach to reduce auditory hallucinations and support psychological recovery in patients with schizophrenia. Following the intervention, patients reported a significant decrease in the intensity of their hallucinations. Emotional reactions were notably less intense, and patients displayed improved emotional regulation and greater behavioral control. The results suggest that murottal audio therapy using Surah Ar-Rahman is an effective non-pharmacological intervention that not only reduces the intensity of auditory hallucinations but also plays a supportive role in the psychological recovery of patients with schizophrenia. The findings emphasize the importance of integrating spiritual therapies into comprehensive treatment plans, as they offer a holistic approach to managing schizophrenia. This intervention can complement traditional pharmacological treatments, providing patients with a sense of spiritual calm and emotional stability, which can enhance their overall mental health and well-being.